2018
DOI: 10.1136/bjophthalmol-2017-311785
|View full text |Cite
|
Sign up to set email alerts
|

Contrast sensitivity and visual acuity under low light conditions in macular telangiectasia type 2

Abstract: Background/AimMacular pigment optical density (MPOD) is centrally depleted early on in macular telangiectasia type 2 (MacTel). Contrast sensitivity (CS) might be related to MPOD, and thus impaired in early MacTel. The effect of low luminance was assessed on both CS and best corrected visual acuity (BCVA).MethodsThis is a cross-sectional study. Pelli-Robson charts were used for CS testing at 1 m in photopic (110 lux) and mesopic (1 lux) conditions. BCVA was tested with ETDRS charts and low luminance visual acui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 23 publications
2
19
0
Order By: Relevance
“…This finding is interesting and important, because we were previously able to show a marked loss of the Stiles-Crawford effect and an impairment of low luminance contrast sensitivity in those eyes of the same observers. 6,8 The impaired contrast sensitivity as opposed to the unimpaired microperimetry sensitivity are indicative of a (postreceptorally) impaired cone system, which would also be in keeping with recent electrophysiological findings in MacTel suggesting an inner retinal dysfunction. 17 Eyes with only minor MPOD loss (class 1) showed a general loss of cyan sensitivity but normal red sensitivity, whereas eyes with more pronounced MPOD loss (classes 2 and 3) showed focal loss of red sensitivity and (more pronounced) loss of cyan function (Fig.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…This finding is interesting and important, because we were previously able to show a marked loss of the Stiles-Crawford effect and an impairment of low luminance contrast sensitivity in those eyes of the same observers. 6,8 The impaired contrast sensitivity as opposed to the unimpaired microperimetry sensitivity are indicative of a (postreceptorally) impaired cone system, which would also be in keeping with recent electrophysiological findings in MacTel suggesting an inner retinal dysfunction. 17 Eyes with only minor MPOD loss (class 1) showed a general loss of cyan sensitivity but normal red sensitivity, whereas eyes with more pronounced MPOD loss (classes 2 and 3) showed focal loss of red sensitivity and (more pronounced) loss of cyan function (Fig.…”
Section: Discussionsupporting
confidence: 67%
“…7 Low light conditions have an overly negative effect on contrast sensitivity and visual acuity in MacTel patients compared with controls. 8 Recently, a two-color dark-adapted fundus-controlled perimetry device was introduced that combines the advantage of fundus-controlled perimetry (socalled microperimetry) with the possibility of retinal sensitivity testing under light-and dark-adapted conditions (so-called scotopic microperimetry). 9 In microperimetry, as opposed to conventional perimetry, stimuli are directly projected onto the retina, which allows creating precise retinal sensitivity maps.…”
mentioning
confidence: 99%
“…In five studies, LLD has been shown to be a strong predictor of geographic atrophy progression and subsequent VA loss 10,38,39,41,43 . LLD is significantly reduced in patients with macular telangiectasia type 1, choroideremia and pseudoxanthoma elasticum when compared with healthy controls 44,45,50 . LLVA has been recommended as a clinical trial outcome measure for dry AMD, geographic atrophy and retinitis pigmentosa 25,37,75 .…”
Section: Discussion and Critical Reviewmentioning
confidence: 99%
“…However, most studies delivering useful insights into the impact of luminance levels on VA included only small participant numbers 5,8 . Similarly, in those studying rare diseases, large sample sizes are not feasible, but results can still be valuable 44,45,47,50 …”
Section: Limitationsmentioning
confidence: 99%
“…Interestingly, an increasing number of studies have explored how CS is altered by extreme environmental conditions, such as low oxygen (Benedek et al., 2002; Pescosolido et al., 2015), sleep deprivation (Koefoed et al., 2015), display terminal fatigue (Gur & Ron, 1992), high gravity (Chou et al., 2003), low light (Müller et al., 2019), and glare (Finlay & Wilkinson, 1984; Puell et al., 2006). The current study is mainly focused on the effect of glare on CS.…”
mentioning
confidence: 99%